Pseudomonas citronellolis; a multi-metal resistant and potential plant growth promoter against arsenic (V) stress in chickpea - Adhikary, Arindam (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.